2017
DOI: 10.1128/mbio.00056-17
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus Trehalose-Regulatory Subunit Homolog Moonlights To Mediate Cell Wall Homeostasis through Modulation of Chitin Synthase Activity

Abstract: Trehalose biosynthesis is found in fungi but not humans. Proteins involved in trehalose biosynthesis are essential for fungal pathogen virulence in humans and plants through multiple mechanisms. Loss of canonical trehalose biosynthesis genes in the human pathogen Aspergillus fumigatus significantly alters cell wall structure and integrity, though the mechanistic link between these virulence-associated pathways remains enigmatic. Here we characterize genes, called tslA and tslB, which encode proteins that conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 74 publications
(124 reference statements)
2
39
0
Order By: Relevance
“…Trehalose pathway is clearly associated with cell wall components, including chitin and beta-glucan, as shown in many previous reports [ 18 , 19 , 42 , 47 ]. Disturbance in substrates of trehalose or enzymes or proteins associated with the trehalose pathway in Aspergillus fumigatus would lead to changes in the cell wall components and structure [ 18 , 19 , 42 , 47 ]. Furthermore, trehalose level and proteins associated with the trehalose pathway may affect exopolysaccharide galactosaminogalactans (GAGs), which are important for fungal adherence and biofilm formation, as shown in A. fumigatus previous reports [ 42 , 47 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Trehalose pathway is clearly associated with cell wall components, including chitin and beta-glucan, as shown in many previous reports [ 18 , 19 , 42 , 47 ]. Disturbance in substrates of trehalose or enzymes or proteins associated with the trehalose pathway in Aspergillus fumigatus would lead to changes in the cell wall components and structure [ 18 , 19 , 42 , 47 ]. Furthermore, trehalose level and proteins associated with the trehalose pathway may affect exopolysaccharide galactosaminogalactans (GAGs), which are important for fungal adherence and biofilm formation, as shown in A. fumigatus previous reports [ 42 , 47 ].…”
Section: Discussionsupporting
confidence: 71%
“…Disturbance in substrates of trehalose or enzymes or proteins associated with the trehalose pathway in Aspergillus fumigatus would lead to changes in the cell wall components and structure [ 18 , 19 , 42 , 47 ]. Furthermore, trehalose level and proteins associated with the trehalose pathway may affect exopolysaccharide galactosaminogalactans (GAGs), which are important for fungal adherence and biofilm formation, as shown in A. fumigatus previous reports [ 42 , 47 ]. In this study, we also observed that validamycin A decreased fungal adherence ( Figure 4(c) ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of glycogen for filamentous fungal pathogenesis has been reported previously in plant pathogens (30). Similarly, trehalose is important for germination and for establishing an infection (28, 29, 69, 70). In conclusion, this study reports on the mechanistic signaling and regulation events underlying A.…”
Section: Discussionmentioning
confidence: 99%
“…The radial growth in the calcofluor white medium was relatively more in the deletion and truncated mutants as compared to the wild-type strain indicating that they are capable of resisting it. Inappropriate accumulation of trehalose, glycerol and other osmolytes have been known to regulate stress responses [19][20][21][22]. Intercellular trehalose plays a critical role in free radical scavenging, whereas glycerol affirmatively responds to osmotic stress [23].…”
Section: Discussionmentioning
confidence: 99%